Comparison of knee society scores in osteoarthritis patient before and after total knee arthroplasty: a case report - I Dewa Gede Indra Pratama Putra; Dewa Gede Kurnia Pratama; Putu Budi Sucitra (DiscoverSys Inc., 2022)
Introduction: Osteoarthritis is a degenerative disease characterized by joint pain in the cartilage. It requires further management, especially in severe conditions that have not responded to pharmacological therapy, such as Total Knee Arthroplasty (TKA). Therefore, the authors aim to compare the knee quality of patients with Knee Society Scores (KSS) before and after TKA surgery. Case description: Female patient, 55 years old, came with the chief complaint of stiffness and pain in both knees for the last two years. The patient had previously undergone regular treatment and is now getting worse. The radiological found the impression of right and left knee osteoarthritis was grade IV, and the KSS assessment results were 40. The patient was then treated with TKA surgery. After the total knee arthroplasty procedure was observed for one month, the patient had no complaints of joint stiffness and did not feel severe pain in both knees. The KSS assessment results were 71 with good interpretation results. Conclusion: There was an improvement in the knee quality of patients with KSS before and after TKA surgery.